Seamless transitions between grid-following and grid-forming control for wind turbines: A novel switching metric and smooth control strategy - Fang, Xinglong; Hu, Yang; Song, Ziqiu; Liu, Jizhen (Renewable energy, 2026)
As the share of wind energy in the power grid increases, the overall strength of the grid tends to decrease, thereby intensifying the stability challenges encountered by conventional grid-following (GFL) wind turbines (WTs). Empirical studies have indicated that grid-forming (GFM) control mechanisms provide enhanced stability in environments characterized by weak grid conditions. Therefore, it is imperative to investigate a switching control strategy for GFL/GFM WTs to improve their adaptability to fluctuations in grid strength. Nonetheless, the switching process may lead to issues such as overvoltage and overcurrent, which could result in irreversible damage to hardware components. In light of this, the present paper proposes a seamless switching control strategy aimed at bolstering the stability and safety of the system in complex operational environments. The study begins with an eigenvalue analysis to assess the grid-integrated characteristics of both GFL and GFM units. Following this analysis, a novel switching metric is introduced. Furthermore, a smooth switching control strategy is proposed to alleviate the overcurrent phenomenon during the transition phase by compensating for voltage and frequency through a consistency algorithm. Experimental findings demonstrate that the proposed switching metric and smoothing control strategy provide a more precise evaluation of the switching requirements for WTs across various operational modes, significantly reducing switching time in comparison to traditional approaches. Additionally, the new switching metric and smoothing control strategy substantially improve the performance indices related to system switching.